Analisis Perbandingan Kecepatan Transfer Data Dengan Kabel USB Tipe A Dan USB Tipe C - Rizal Nur Alfi; Kartika Hijjayanti; Nurrochmat Saptoaji; Adhi Rizal (NJCA (Nusantara Journal of Computers and Its Applications), 2019)
Every technology device these days should have a lot of components which support the performance of the devices, one of the components is Universal Serial Bus or known as USB. USB is a communication protocol on a device that can be use as a connection between devices. There's a lot of type from USB it self, such as USB type A and USB type C, and both have their own capabilities. We can find USB type A are still used this time especially on smartphones, but slowly we can feel the impact of appearence of USB type C is can shift the position of USB A because of its superior ability compared to USB A. According to that, it have been tested between cables with USB A connector and USB C connector with experimental research to find out the quality of USB as seen from the transfer rates of the two types of USB. The result of the experiment, explains that USB cable with type A connector is faster than USB type C. Results of the experiment are inversely proportional to the theory because of many factors that influence.